FEATURES OF THE RULES FOR INSULIN INJECTION TECHNIQUES IN ELDERLY AND SENILE PATIENTS WITH DIABETES MELLITUS - Negmatova , Gulzoda Shukhratovna; Xakimova , Gulira’no Dilshodbek qizi; Abdiyev , Lazizbek Sobir oʻgʻli; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
Currently, one of the pressing problems of humanity is diabetes mellitus (DM). The number of patients with diabetes in the world doubles every 10-15 years. The development of diabetes and its complications leads to disability of patients and a deterioration in the quality of life. However, every year, thanks to the efforts of scientists, new drugs and methods of treating this disease, based on modern scientific achievements, appear.